The implementation of the Merdeka curriculum: Impacts of pedagogical, professional, and social competencies - Arianto, Dodi; Syahrastani; Gusril; Firdaus, Kamal (Universitas Jambi, Indonesia, 2024)
This research examines the influence of physical education teachers' pedagogical, professional, and social competence on the Merdeka Curriculum in State Middle Schools throughout Agam Regency. This research used a quantitative approach with a comparative causal design and involved 30 physical education teachers as respondents. Data were collected through questionnaires and analyzed using descriptive statistical techniques, normality tests, linearity tests, and path analysis. The research results show that pedagogical competence directly and significantly influences the Merdeka Curriculum. Likewise, professional and social competence are affected. Additionally, there is a significant indirect influence, where pedagogical and professional competencies have an impact through social competencies. This research concludes that physical education teachers' pedagogical, professional, and social competencies have a crucial role in supporting the implementation of the Merdeka Curriculum. Physical education teachers need to continue to improve their competence, especially in the pedagogical aspect, to ensure the successful implementation of the Merdeka Curriculum at the middle school level.